4-Year Outcome Analysis of Endoscopic Vein Harvesting for Coronary Artery Bypass Grafting. (20th March 2013) - Raja, Shahzad G.; Rochon, Melissa; Sproson, Camilla; Bahrami, Toufan T.
Abstract : Objective . Despite increasing recognition that endoscopic vein harvesting (EVH) is associated with decreased leg wound morbidity, improved cosmetic results, and enhanced patient satisfaction, concerns persist regarding the safety and efficacy of EVH. This study compares in-hospital and midterm outcomes for EVH and open vein harvesting (OVH) at our institution. Methods . 772 patients with EVH were propensity matched to 772 patients who had OVH. Their data were prospectively entered into the cardiac surgery database (PATS; Dendrite Clinical Systems, Ltd., Oxford, UK) and analyzed, retrospectively. The mean duration of followup was 26.4 ± 10.3 months. Results . EVH was associated with a significant reduction in rate of donor site infection compared to OVH (0.39% versus 3.9%, P < 0.001 ). Short- and medium-term vein graft patency was similar. After adjusting for clinical covariates, EVH did not emerge as an independent predictor of readmission to hospital for cardiac causes (odds ratio (OR) 1.19, 95% confidence interval (CI) 0.96–1.58, and P = 0.31 ), medium-term mortality (hazard ratio (HR) 1.28, 95% CI 1.09–1.42, and P = 0 . 92 ), and need for reintervention (HR 1.21, 95% CI 0.98–1.32, and P = 0 . 86 ). Risk-adjusted survival was 94% for EVH patients and 93% for OVH patients (P = 0 . 96 ) during the medium-term followup. Conclusion . Our analysis confirms the short- and midium-term safety and efficacy of EVH.